Monetary Policy, Debt Management and Capital Allocation: The Implications of Behavior in the Financial Sector and Substitutability Between Securities - Silber, William Leo (Journal of Finance, 1967)
William Leo Silber, Monetary Policy, Debt Management and Capital Allocation: The Implications of Behavior in the Financial Sector and Substitutability Between Securities, The Journal of Finance, Vol. 22, No. 4 (Dec., 1967), pp. 699-700